2020
DOI: 10.3390/toxins12090574
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Melittin Protects against Cisplatin-Induced Acute Kidney Injury in Mice via the Regulation of M2 Macrophage Activation

Abstract: Inflammation is an essential biological response that eliminates pathogenic bacteria and repairs tissue after injury. Acute kidney injury (AKI) is associated with systemic and intrarenal inflammation as the inflammatory process decreases renal function and promotes progression to advanced chronic kidney disease. Macrophages are key mediators of the inflammatory response; their activation influences the immune system and may have various effects. Classically activated type I macrophages (M1) produce a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…A total of 11 studies were published. Three reviews provided a good overview of the therapeutic effect of bee venom [ 6 , 7 , 8 ], and eight original research articles focused on bee venom, melittin, PLA 2 , and apamin [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 11 studies were published. Three reviews provided a good overview of the therapeutic effect of bee venom [ 6 , 7 , 8 ], and eight original research articles focused on bee venom, melittin, PLA 2 , and apamin [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…Third, Zorila et al [ 16 ] used spectral analysis of Laurdan fluorescence to demonstrate that melittin could induce local order changes in artificial and biological membranes. Finally, Kim et al [ 12 ] examined the role of melittin in cisplatin-induced acute kidney injury and showed that intraperitoneal administration of different doses of melittin could inhibit cisplatin-induced increase in creatinine and blood urea nitrogen by regulating M2 macrophage expression.…”
mentioning
confidence: 99%
“…In addition to PLA2, as an active component of BV, modulating Treg cells in some neuroin ammatory disease models, including Alzheimer disease (Baek et al, 2018) and Parkinson's disease (Chung et al, 2012) models and therefore BV can rescue dopaminergic neurons from injury or neurodegeneration, melittin can modify the release and production of different cytokines; it was found to increase levels of the antiin ammatory cytokine IL-10 and prevent the release of the proin ammatory cytokines IL-6 and IL-1β (Kim et al, 2020). In addition, BV restores the brain's neurochemistry and ameliorates all changes in neuroin ammatory biomarkers in rotenone-induced Parkinson's disease (Khalil et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotoxicity from snake venom can have several origins such as impaired perfusion due to intravascular coagulation, direct action of venom cytotoxic components on renal structures, and either hemoglobin or myoglobin deposits onto proximal and distal renal tubule. Another possible renal failure cause refers to cardiotoxins and nephrotoxic components in these animals venom [ 35 , 37 ]. Some studies evaluated dissimilar venom fractions in different animals and their findings point to changes in renal hemodynamics as well as proximal and distal renal tubular degeneration [ 33 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there is clinical and experimental evidence of venoms from different snakes that cause acute kidney damage [4,[33][34][35][36]. While envenoming refers to components causing neurotoxic manifestations, other other systemic manifestations are equally present [37], whose pathways are reviewed in [38].…”
Section: Snakesmentioning
confidence: 99%